A comprehensive numerical study on the subcooled falling film heat transfer on a horizontal smooth tube. (April 2018) - Zhao, Chuang-Yao; Ji, Wen-Tao; He, Ya-Ling; Zhong, Ying-Jie; Tao, Wen-Quan
Highlights: A comprehensive numerical study on the subcooled falling film heat transfer on a horizontal smooth tube is conducted. The role of surface tension in the calculation of falling film heat transfer is discussed. A heat transfer correlation considering a multitude of factors is developed. Abstract: The effects of film flow rate, heat flux, inlet liquid temperature, tube diameter and liquid distributor height on subcooled falling film heat transfer outside a horizontal smooth tube are numerically studied, and a heat transfer correlation based on the current data is developed. Comparisons between the predicted results and the published experimental data in the literature are also conducted. The calculation ranges are: film flow rate from 0.025 to 0.284 kg m −1  s −1, heat flux from 1.0 to 100 kW m −2, inlet liquid temperature from 2 to 104 °C, tube diameter from 6.35 to 50.8 mm and liquid distributor height from 3.0 to 50.8 mm. The results indicate that: (1) the numerical results of the local heat transfer coefficient are in good agreement with the experimental data in the literature; (2) the surface tension plays an important role in the calculations of heat transfer in two stagnation zones, (3) the heat transfer coefficient shows four distinct zones along with peripheral angle: stagnation zone, impingement zone, thermal layer development zone and departure zone; (4) the heat transfer coefficient increases with increase in film flow rate, tube diameter or liquid distributor height, while keeps constant with increasing heat flux; (5) the correlation predicts 92% of the total 141 calculated data with deviations within ±10%, and predicts 78% of 284 data available in literature with deviations within ±30%.